Characteristics and Manufacturability of Duplex Stainless Steel: A Review - Patra S.; Agrawal A.; Mandal A.; Podder A.S. (My University, 2025)
Duplex stainless steels (DSS) have been growing continuously as they are cost effective alternative to austenitic stainless steel with better mechanical and corrosion resistance. Duplex stainless steel compositions are expanding in both directions towards leaner and richer chemistry for popular as well as very critical applications. The strength of DSS is its high yield strength compared to popular austenitic series and corrosion resistance particularly pitting and chloride stress corrosion cracking. Challenges of DSS remain in the embrittlement phase formation during the manufacturing of highly alloyed DSS, hot cracking and formability of the steel. Super duplex and hyper duplex steels are finding extremely critical application due to their good mechanical properties and corrosion resistance even replacing Nickel based alloys and Ti alloys in few applications. The paper reviews the characteristics and manufacturability of duplex stainless steel including recent developments. © 2021, The Indian Institute of Metals - IIM.